Design and Implementation of Wireless 4-20 mA Current Simulator - Nassiriyah, Ali F. Halihal (Iraqi Journal for Electrical and Electronic Engineering, 2018)
This paper presents new device to simulate and inject a 4-20 mA current signal to PLC and control on this signal wirelessly. The proposed simulator device has been designed and implemented by a PIC 18f4520 microcontroller and an Ethernet click. This device is connected to Wireless Local Area Network (WLAN) via Wi-Fi router using TCP/IP protocol. The simulator has two channels for 4-20 mA current output signals with two channels for digital output signals, controlled by a laptop or a smart mobile. The purpose of this work is to demonstrate the usefulness of the Wi-Fi wireless technology for remote controlling on the 4-20 mA output current signal and the digital output signal in the designed simulator device. The experiments indicate that the proposed wireless simulator outputs the 4- 20 mA current with high accuracy and very fast response. The experiments also indicate that the proposed wireless simulator is easy, comfortable and convenient practically to use in the test operations of protections, interlocks and integrity of analog input channels for PLC compared to the wired simulator.